TOTAL THYROIDECTOMY AS PRIMARY ELECTIVE PROCEDURE IN MULTINODULAR THYROID DISEASE - Sheikh, Irfan Ali; Waleem, Sheikh Saadat Ullah; Haider, Irfan Zafar; Haroon, Asna; Ashfaq, Muhammad (Journal of Ayub Medical College Abbottabad, 2009)
Background: Multinodular goitre is one of the commonest thyroid diseases encountered in the practice of surgery. The most common surgery being performed for multinodular goitre is subtotal thyroidectomy. Total thyroidectomy is designed to remove all of the thyroid tissue. The objective of this study was to evaluate total thyroidectomy as a primary elective procedure for treatment of multinodular thyroid disease. This descriptive study was carried out at Combined Military Hospital Rawalpindi from June 2003 to September 2006. Methods: 88 patients of multinodular thyroid disease were included. Patients having evidence of recurrent laryngeal nerve damage, recurrent goitre, evidence of altered parathyroid functions or evidence of malignancy were excluded. All patients underwent total thyroidectomy by the same team of surgeons and the patients were closely followed up for postoperative complications especially in terms of recurrent laryngeal nerve damage and hypocalcaemic tetany. Results: No major postoperative complication was noted. Only 1 patient (1.14%) developed unilateral recurrent laryngeal nerve damage and 2 patients (2.27%) developed transient hypocalcaemia that recovered quickly. Conclusion: Total thyroidectomy as a primary elective procedure in multinodular thyroid disease is a safe option and it removes the disease process completely, lowers local recurrence rates and avoids the substantial risks of reoperative surgery. Keywords: Multinodular goitre, Total thyroidectomy, Primary elective total thyroidectomy.